Students' Perceptions on Online Learning During the COVID-19 Pandemic - Fathia Natasa (Journal of English Development, 2022)
Abstract The impossibility to continue the conventional classroom created an inevitable situation where online learning is the most suitable solution at the moment to keep up the learning process amidst the pandemic. It is presumably familiar to students, but the sudden change of online learning being applied sporadically to regularly arise an issue of how the students perceive, access, react to it and the challenges they face. This study aims to find out students’ perceptions on online learning during the COVID-19 pandemic and the subject of the study is students of the English Study Program of Riau University. Descriptive approaches to quantitative methods were used in this study. Google form was used to collect the data and there were 127 students that participated in filling out the questionnaire. SPSS 26 was used to analyze the collected data. The findings revelead that students’ perceptions were negative toward online learning. The three main reasons affecting the result were the lack of enthusiasm, internet sustainability, and technical issues.